Global error bounds for the extended vertical LCP of ∑−SDD matrices - Mengting Gan (AIMS Mathematics, 2024)
An error bound for the solution of the $ \sum-SDD $ matrix extended vertical linear complementarity problem is given when the $ \sum-SDD $ matrix satisfies the row W-property. It is shown by the illustrative example that the new bound is better than those in [1] in some cases.